Integrasi Pembelajaran Dengan Penelitian Dan Pengabdian Kepada Masyarakat - Muflihah, Muflihah; Sholehan, Sholehan (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2023)
The integration of research and devotion to society in the learning process become a necessity for university. Universities in Indonesia have carried out an integrated learning process with studies and devotees to communities such as the state islamic university of sunan ampel surabaya and the state islamic university of maulana malik Ibrahim Malang. The concept of integration in the learning process was carried out to support the implementation of the tri dharma administration of the University and to suit the need for internal quality audits and accreditation of BANPT. This study is a kind of descriptive quantitative research. The results from this study are in form of integrating study with study and service to society in RPS of Arabic education department of UINSA and UINMA in luring, face to face, learning activities, structured assignment and the independent assignment.its output can be in form of artiker in a research journal and service learning in schools, a equivalency teaching in schools and interning for an integrated RPS learning output in community service.